2017
DOI: 10.1002/pd.5189
|View full text |Cite
|
Sign up to set email alerts
|

The 2D axial transverse views of the fetal face: A new technique to visualize the fetal hard palate; methodology description and feasibility

Abstract: The ATV is an easy, simple, and accessible 2D method to visualize the FHP with no additional time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…We completely agree with the conclusion stated by the authors “… This easy and accessible technique, according to the angle of insonation, enables to overcome the main difficulty in that situation: the shadowing of the maxillar ridge. Images are of true quality and could be obtained by sonographers with no 3D experience and during routine scan ….” Our study provide further support to this notion, both by plotting a growth curve of reproducible measurements obtained during 2D routine obstetric scans, from as early as 14 weeks gestation, and by the prenatal diagnosis of secondary palate clefts by using only these direct 2D images.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We completely agree with the conclusion stated by the authors “… This easy and accessible technique, according to the angle of insonation, enables to overcome the main difficulty in that situation: the shadowing of the maxillar ridge. Images are of true quality and could be obtained by sonographers with no 3D experience and during routine scan ….” Our study provide further support to this notion, both by plotting a growth curve of reproducible measurements obtained during 2D routine obstetric scans, from as early as 14 weeks gestation, and by the prenatal diagnosis of secondary palate clefts by using only these direct 2D images.…”
Section: Discussionsupporting
confidence: 61%
“…Pilu and Segata called it the angled insonation approach in their 3D US volume acquisition, enabling them to avoid shadowing within the reconstructed multiplanar view of the secondary palate. Recently, Tutschek and Blaas further demonstrated how this insonation approach, enables a shadow free volume, once initiated from the same plane as Fuchs et al described in their 2D series of mid trimester scans. In that study by Fuchs et al, the authors showed that a direct 2D visualization of the secondary palate is feasible in 95% of cases during second trimester scans, at first attempted.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…When an orofacial cleft lip is discovered, precise characterization of this malformation is necessary and especially the extension of this cleft to the secondary palate. Assessing the secondary fetal palate can be performed through a two‐dimensional (2D) ultrasound technique or by the use of multiplanar or tomographic reconstructions provided by three‐dimensional (3D) ultrasonography …”
Section: Introductionmentioning
confidence: 99%
“…Regarding the visualization of the secondary palate, the main reasons for failure advocated by sonographers are not only the difficulty of obtaining a clear image of the palate, but also ensuring that the palate structure is correctly identified. Recently, we published a study demonstrating that visualization of the fetal hard palate through an axial transverse 2D view was feasible in 95% during routine second‐trimester scans …”
Section: Introductionmentioning
confidence: 99%